Regulation of IL-17 in autoimmune diseases by transcriptional factors and microRNAs - Khan, Deena; Ansar Ahmed, S. (Frontiers in Genetics, 2015)
In recent years, IL-17A (IL-17), a pro-inflammatory cytokine, has received intense attention of researchers and clinicians alike with documented effects in inflammation and autoimmune diseases. IL-17 mobilizes, recruits and activates different cells to increase inflammation. Although protective in infections, overproduction of IL-17 promotes inflammation in autoimmune diseases such as multiple sclerosis, rheumatoid arthritis, psoriasis, among others. Regulating IL-17 levels or action by using IL-17-blocking antibodies or IL-17R antagonist has shown to attenuate experimental autoimmune diseases. It is now known that in addition to IL-17-specific transcription factor, RORγt, several other transcription factors and select microRNAs (miRNA) regulate IL-17. Given that miRNAs are dysregulated in autoimmune diseases, a better understanding of transcriptional factors and miRNA regulation of IL-17 expression and function will be essential for devising potential new therapies. In this review, we will overview IL-17 induction and function in relation to autoimmune diseases. In addition, current findings on transcriptional regulation of IL-17 induction and plausible interplay between IL-17 and miRNA in autoimmune diseases are highlighted.